A STUDY ON THE ABILITY OF POLYSYLLABIC ADJECTIVE WORDS STRESS PLACEMENT OF ENGLISH STUDY PROGRAM STUDENTS - Puspita, Sari; Dahnilsyah, Dahnilsyah; Mariasyafriyanti, Mariasyafriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research concerned with the student’s knowledge on the polysyllabic adjective word stress placements of English Education Study Program Students. This research was a descriptive with quantitative approach. The research was conducted on English Study Program of Universitas Riau. The selected sample was Class of B English Study Program which consist of 34 students. The sample is selected by using cluster random sampling technique. Thirty-four students involved in this study were given the instrument of stressing test. The data were collected by using WhatsApp and Google Drive. The collected data were analyzed by three raters and the result were calculated by using Microsoft Excel. The results of this study shows that the ability of the Second-year Students of English Study Program on polysyllabic adjective words stress placements was categorized Very Good level with 86,79 of the total average score. Furthermore, the test result among 3 syllables and 4 syllables polysyllabic adjective words shows that the second-year students of English Study Program made many incorrect stress placements in 4 syllables words.Key Words: Stress, Polysyllabic Adjective words